2023
DOI: 10.1029/2022cn000176
|View full text |Cite
|
Sign up to set email alerts
|

Even a Blind Chicken Sometimes Finds a Grain of Corn—In My Case in Space

Abstract: Sometimes you need to take strategic risks even though you cannot know in advance where they will lead. I left my comfortable city life in Helsinki for a PhD position in space physics far away in the Arctic. The first part of the title of this paper is a compliment—originally a German proverb—a throwaway comment from a professor in connection with my decision. Good luck also helps. When I was appointed as a university lecturer, I did not have a clue about a new law in Sweden opening the possibility for promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…As we noted above, head echoes correspond to the detection of the ionization associated with the meteoroid itself. These are readily detected by High-Power Large-Aperture (HPLA) narrow-beam radars such as the EISCAT, MAARSY, and Jicamarca radars [73,74]. Ref.…”
Section: Narrow-beam St and Mst Radarsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we noted above, head echoes correspond to the detection of the ionization associated with the meteoroid itself. These are readily detected by High-Power Large-Aperture (HPLA) narrow-beam radars such as the EISCAT, MAARSY, and Jicamarca radars [73,74]. Ref.…”
Section: Narrow-beam St and Mst Radarsmentioning
confidence: 99%
“…Ref. [73] gives an entertaining discussion of the early observations of head echoes with the EISCAT radar. Head echoes are also clearly detected with some smaller radars (e.g., [25,27,75]), and the Adelaide ST narrow-beam radar results also demonstrated that a HPLA radar was not needed to do this.…”
Section: Narrow-beam St and Mst Radarsmentioning
confidence: 99%